Improvement of Erosion-Corrosion Behavior of AISI 420 Stainless Steel by Ion-Assisted Deposition ZrN Coatings - Yuntao Xi (MDPI AG, 2021)
In this paper, a pragmatic technique has been developed to evaluate the erosion-corrosion behavior of three kinds of ZrN coatings (i.e., monolayer, multilayer, and gradient layers) which were deposited on AISI 420 martensitic stainless steel using an ion-assisted deposition technology. Among them, the monolayer coating refers to the coating with no change in composition and structure, the multilayer coating refers to the coating with alternating change of Zr/ZrN, and the gradient coating refers to the ZrN coating by increasing N2 partial pressure gradually. The morphology, composition, and microhardness of these ZrN coatings were examined by means of integrating the scanning electron microscopy (SEM), X-ray diffraction (XRD), and Knoop hardness measurements, while anodic polarization tests and salt fog spray tests in a simulated industrial environment have been performed to evaluate and identify the corrosion mechanisms of these coatings. The surface microhardness and corrosion resistance of the AISI420 martensitic stainless steel is found to be significantly improved by depositing the ion-assisted deposition ZrN coatings. The study indicates that the erosion-corrosion behavior in the slurry is the result of the synergistic effect of small-angle erosion and acid solution corrosion. Three ZrN coatings hinder the slurry erosion-corrosion behavior from two aspects (i.e., erosion resistance of small-angle particles as well as corrosion resistance of the substrate), thereby significantly improving the erosion-corrosion resistance of AISI 420 stainless steel. In addition, the ZrN gradient coatings show a much better erosion-corrosion resistance than that of the monolayer/multilayer ZrN coating because they have excellent crack resistance, bearing capacity, and electrochemical performance.